Precise estimation of fine-scale urban street tree structure and woody aboveground biomass with backpack LiDAR - Jinming Yang; Tianhui Zhang; Bojian Wang; Feng Cheng; Mathieu Decuyper; Linqian Yu; Huicui Lu; Haifang Li; Richard Hauer (Urban Ecosystems, 2026)

Understanding forest transitions and lock-ins in Latin American agro-forest frontiers: aligning theory to practice for accelerating restoration - Madelon Lohbeck; Thomas W. Kuyper; Frans Bongers; Rocío Aguilar-Fernández; Patricia Balvanera; Jelle Behagel; Carolina Berget; Felix Bianchi; Irene Maria Cardoso; Lucas de Carvalho Gomes; Juana Cruz-Morales; Mathieu Decuyper; et al. (Global Environmental Change, 2026)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Dissecting forest transition: Contribution of mature forests, second-growth forests and tree plantations to tree cover dynamics in the tropics - Johan de Jong; Lourens Poorter; Wil de Jong; Frans Bongers; Madelon Lohbeck; Elmar Veenendaal; Jorge A. Meave; Catarina C. Jakovac; Pedro H.S. Brancalion; Lucy Amissah; Miguel Martínez-Ramos; Harm Bartholomeus; et al. (Land Use Policy, 2025)

ENSO Wildfires Impact Amazonian Floodplains in Complex Ways - Peter van der Sleen; Mathieu Decuyper; Bernardo M. Flores; J. Ethan Householder; Milena Holmgren (Ecosystems, 2025)
Amazonian floodplains are the most extensive and biodiverse riverine habitat on Earth. They currently face unprecedented fire regimes as climate change increases the frequency and intensity of drought. While it is clear that fire impacts on floodplain ecology can be severe, fire regimes and their effect on forest ecosystems have yet to be fully examined across the considerable spatial and ecological heterogeneity of Amazonian floodplains. We used the MODIS burned area product to map fire occurrence across Amazonian floodplain forests. Next, we assessed forest recovery after burning using NDVI values from LandSat images. We specifically focused on differences in wildfire dynamics and forest recovery after burning across floodplains associated with the three main river types in the Amazon basin (black-, clear-, and white-water rivers). We found that the occurrence of forest fires in floodplains is strongly associated with ENSO events and increases as land-use intensity increases, dry seasons get longer, soils become sandier, and the synchrony between flooding and precipitation patterns increases. Postfire forest recovery is slower, and reburning risk is higher, on nutrient-poor floodplains of black-water rivers, compared to the nutrient-richer floodplains of white- and clear-water rivers. Moreover, forest recovery is significantly slower in regions flooded for prolonged periods, regardless of river type. Our results call for urgent prevention and monitoring of floodplain forest fires across the Amazon basin, with particular attention to black-water floodplains, to prevent large-scale vegetation shifts and cascading ecosystem changes on biodiversity and ecosystem services provided by floodplain forests.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Thermal Infrared Remote Sensing of Stress Responses in Forest Environments: a Review of Developments, Challenges, and Opportunities - Magdalena Smigaj; Avinash Agarwal; Harm Bartholomeus; Mathieu Decuyper; Ahmed Elsherif; Arjen de Jonge; Lammert Kooistra (Current Forestry Reports, 2023)
Purpose of Review The successful application of thermal infrared (TIR) remote sensing in the agricultural domain, largely driven by the arrival of new platforms and sensors that substantially increased thermal data resolution and availability, has sparked interest in thermography as a tool for monitoring forest health. In this review, we take a step back to reflect on what physiological responses are reflected in leaf and canopy temperature and summarise research activities on TIR remote sensing of stress responses in forest environments, highlighting current methodological challenges, open questions, and promising opportunities. Recent Findings This systematic literature review showed that whilst the focus still remains on satellite imagery, Uncrewed Aerial Vehicles (UAVs) are playing an increasingly important role in testing the capabilities and sensitivity to stress onset at the individual tree level. To date, drought stress has been the focal point of research, largely due to its direct link to stomatal functioning at leaf level. Though, research into thermal responses to other stressors, e.g. pathogens, is also gaining momentum. Summary Disentangling stress-induced canopy temperature variations from environmental factors and structural influences remains the main challenge for broader application of TIR remote sensing. Further development and testing of approaches for thermal data analysis, including their applicability for different tree species and sensitivity under different climatic conditions, are required to establish how TIR remote sensing can best complement existing forest health monitoring approaches.

Forest disturbance and recovery in Peruvian Amazonia - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Mathieu Decuyper; Natalia Málaga; Patricia Durán Montesinos; Alexs Arana Olivos; Ricardo De la Cruz Paiva; Christopher Martius; Martin Herold (Global Change Biology, 2023)
Amazonian forests function as biomass and biodiversity reservoirs, contributing to climate change mitigation. While they continuously experience disturbance, the effect that disturbances have on biomass and biodiversity over time has not yet been assessed at a large scale. Here, we evaluate the degree of recent forest disturbance in Peruvian Amazonia and the effects that disturbance, environmental conditions and human use have on biomass and biodiversity in disturbed forests. We integrate tree‐level data on aboveground biomass (AGB) and species richness from 1840 forest plots from Peru's National Forest Inventory with remotely sensed monitoring of forest change dynamics, based on disturbances detected from Landsat‐derived Normalized Difference Moisture Index time series. Our results show a clear negative effect of disturbance intensity tree species richness. This effect was also observed on AGB and species richness recovery values towards undisturbed levels, as well as on the recovery of species composition towards undisturbed levels. Time since disturbance had a larger effect on AGB than on species richness. While time since disturbance has a positive effect on AGB, unexpectedly we found a small negative effect of time since disturbance on species richness. We estimate that roughly 15% of Peruvian Amazonian forests have experienced disturbance at least once since 1984, and that, following disturbance, have been increasing in AGB at a rate of 4.7 Mg ha −1 year −1 during the first 20 years. Furthermore, the positive effect of surrounding forest cover was evident for both AGB and its recovery towards undisturbed levels, as well as for species richness. There was a negative effect of forest accessibility on the recovery of species composition towards undisturbed levels. Moving forward, we recommend that forest‐based climate change mitigation endeavours consider forest disturbance through the integration of forest inventory data with remote sensing methods.

Salt-marsh erosion and restoration in relation to flood protection on the Wadden Sea barrier island Terschelling - Jantsje M. van Loon-Steensma; Pieter A. Slim; Mathieu Decuyper; Zhan Hu (Journal of Coastal Conservation, 2014)

Dendrochronology of Atriplex portulacoides and Artemisia maritima in Wadden Sea salt marshes - Mathieu Decuyper; Pieter A. Slim; Jantsje M. Van Loon-Steensma (Journal of Coastal Conservation, 2014)